If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -4 = 6x + -5 Reorder the terms: -4 + 5x = 6x + -5 Reorder the terms: -4 + 5x = -5 + 6x Solving -4 + 5x = -5 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + 5x + -6x = -5 + 6x + -6x Combine like terms: 5x + -6x = -1x -4 + -1x = -5 + 6x + -6x Combine like terms: 6x + -6x = 0 -4 + -1x = -5 + 0 -4 + -1x = -5 Add '4' to each side of the equation. -4 + 4 + -1x = -5 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = -5 + 4 -1x = -5 + 4 Combine like terms: -5 + 4 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| (r-4)(r+18)=-46 | | x/0.008-x | | 3t+19=6t+4 | | 9n+(7n+21)=59 | | 7*c=609 | | 0.5x+0.4y=50 | | 1+3(x-2)=11-9(x-6) | | 7+10k=12k+1 | | -8+4u=-28 | | 4-5y=5y-x | | 15=-7+4v | | 45m^2=9mw | | 8x+8=4x+52 | | 12x^2+2x-4= | | N^2+3N-1=3 | | 8x+3=7x-10 | | 10-2y=40 | | 45m^2=9w | | Log(x+3)+log(x)-1=0 | | 5=2p+q | | f(x)=0.41ln(x+1)+31 | | x+gy=j | | 5(2x+3)+4= | | 12m-16=44 | | b(x)+gy=j | | 14-2y=50 | | X-1/12=5/6 | | 2.9x-3+x-3= | | 4x+12=-53 | | 177+2x=1031 | | 3h+10+2h=2(6-h) | | 5(x-16)=x |